2018
DOI: 10.1111/plb.12905
|View full text |Cite
|
Sign up to set email alerts
|

Breeding systems in Balsaminaceae in relation to pollen/ovule ratio, pollination syndromes, life history and climate zone

Abstract: Pollen/ovule (P/O) ratios are often used as proxy for breeding systems. Here, we investigate the relations between breeding systems and P/O ratios, pollination syndromes, life history and climate zone in Balsaminaceae. We conducted controlled breeding system experiments (autonomous and active self-pollination and outcrossing tests) for 65 Balsaminaceae species, analysed pollen grain and ovule numbers and evaluated the results in combination with data on pollination syndrome, life history and climate zone on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 70 publications
(82 reference statements)
1
17
0
1
Order By: Relevance
“…Even though studies have been focused on understanding the relationships between plant-animal interaction and the evolution of floral traits 1,78,79 , little is known about the relationship between ecological and evolutionary specialization 4 . Our results showed that restrictive flowers were related to higher ecological specialization levels than unrestrictive flowers.…”
Section: Discussionmentioning
confidence: 99%
“…Even though studies have been focused on understanding the relationships between plant-animal interaction and the evolution of floral traits 1,78,79 , little is known about the relationship between ecological and evolutionary specialization 4 . Our results showed that restrictive flowers were related to higher ecological specialization levels than unrestrictive flowers.…”
Section: Discussionmentioning
confidence: 99%
“…Voucher specimens are deposited in the herbarium of Bonn. For genetic analyses, we expanded the phylogenetic data set of Janssens et al (2009 a ) and Lozada-Gobilard et al (2019) (Supplementary data Table S1). Since several newly added taxa are currently in the process of being officially described, they are here indicated with informal names.…”
Section: Methodsmentioning
confidence: 99%
“…Advertisement (Dellinger et al, 2019a) Amount Manual counting or use of a particle counter (e.g. Castellanos et al, 2004) Fresh or ethanol-preserved flower material Efficiency (Cruden, 2000, but also see Lozada-Gobilard et al, 2018) Quality (viability, protein content)…”
Section: Pollinator Observationsmentioning
confidence: 99%
“…Lunau et al, 2015;Konzmann et al, 2019) Pollen kit, viscin threads e.g. Sudan dyes (Pacini & Hesse, 2005) Ethanol-preserved flower material Multifunctional (UV or water loss protection, pollen packaging; reviewed in Pacini & Hesse, 2005) Gynoecium Timing of stigma receptivity Documentation in the field Efficiency (Armbruster et al, 2009) Stigma size or shape Qualitative classification or measurements, scanning electron microscopy Fresh or ethanol-preserved flower material, herbarium specimens Efficiency (Cruden, 2000;Dellinger et al, 2019a) Number of ovules Quantification through microscope or HRX-CT (Staedler et al, 2018) Fresh or ethanol-preserved flower material Efficiency (Cruden, 2000, but also see Lozada-Gobilard et al, 2018) Herkogamy Spatial separation between anthers and stigma Measurements or morphometrics Fresh or ethanol-preserved flower material Efficiency (outcross pollen transfer, Opedal, 2018) Methods, type of floral material needed, and information on comparative or experimental evidence of the functional significance of certain traits in the pollination process are given. Where possible, objective (ideally quantitative) measurements on traits should be prioritised over qualitative categorisation.…”
Section: )mentioning
confidence: 99%